Probing dark sectors with long-lived particles at Belle II - Filimonova, Anastasiia; Schäfer, Ruth; Westhoff, Susanne (Physical review, 2020)
We propose a new search for light scalar singlets in rare meson decays. For couplings well below the electroweak interaction strength, the scalar is long-lived at detector scales and decays into displaced pairs of leptons or light mesons. We show that Belle II has a remarkable potential to probe scalars in the GeV range with couplings as small as 10−5. The predicted sensitivity is higher than at the long-baseline experiments NA62 and FASER and comparable with projections for FASER 2. We also investigate signatures of invisibly decaying scalars in rare meson decays with missing energy.